Biomechanical Properties of the Umbilical Cord and Its Relationship with Perinatal Outcomes - Kanbay Öztürk, Sümeyye; Çakır Köle, Merve; Çelik, Talip; Aksoy, Lale; Demir, Hakan; Çorakçı, Aydın (Anatolian Journal of Obstetrics and Gynecology Research, 2024)
Purpose: The aim of this study was to determine the elasticity modulus of umbilical cord (UC) using biomechanical tests in diabetic, preeclamptic and control groups and to investigate the relationship with perinatal outcomes. Methods: Patient data from diabetic, preeclamptic and healthy control group women, who gave birth in a single center between September and December 2019 were collected. Prenatal demographic data, pregnancy outcome, and ultrasound Doppler pulsatility index (PI) was obtained. Cord samples were taken at birth and newborn morphometric parameters were measured. The diameter of UCs were measured. The samples then underwent biomechanical testing. By calculating strain and stress, the elasticity modulus of samples were derived. Results: There were thirty subjects in each group. Mean UC radius was significantly greater (p<0.01) in the diabetic group (1.03±0.29 cms) compared to control group (0.86±0.21 cms) and preeclamptic group (0.74±0.14 cms). Median (range) elasticity modulus was highest in the preeclamptic vs. the diabetic and control groups [0.28 (0.22-0.34) vs. 0.12 (0.8-0.30) vs. 0.14 (0.12-0.34), respectively; p<0.01]. Increase in birth week (r=-0.26, p=0.01), birthweight (r=-0.42, p<0.01), newborn height (r=-0.38, p<0.01), and UC diameter (r=-0.78, p<0.01) were all negatively correlated with elasticity modulus. Umbilical artery Doppler PI values had weak positive correlation with elasticity modulus (r=0.21, p=0.4). Conclusion: Morphological, mechanical and histological studies were performed on the UC. It appears that the UC its characteristics are changed in disease processes affecting pregnancy. We believe that if ultrasonographic, histological, biochemical and immunohistochemical data are combined with biomechanical data, larger serial studies may provide new parameters with which we can evaluate fetal well-being based on UC characteristics.